2020
DOI: 10.3847/1538-4357/ab74d0
|View full text |Cite
|
Sign up to set email alerts
|

Fast Radio Bursts from Activity of Neutron Stars Newborn in BNS Mergers: Offset, Birth Rate, and Observational Properties

Abstract: Young neutron stars (NSs) born in core-collapse explosions are promising candidates for the central engines of fast radio bursts (FRBs), since the first localized repeating burst FRB 121102 happens in a star forming dwarf galaxy, which is similar to the host galaxies of superluminous supernovae (SLSNe) and long gamma-ray bursts (LGRBs). However, FRB 180924 and FRB 190523 are localized to massive galaxies with low rates of star formation, compared with the host of FRB 121102. Meanwhile, the offsets between the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 129 publications
1
43
0
Order By: Relevance
“…Bhandari et al [165] and Heintz et al [166] agreed that compact merger events (WD-WD, NS-NS mergers), accretion-induced WD collapse and CCSNe seem to be plausible mechanisms for the FRBs localised by ASKAP and that the galaxies hosting LGRBs (faint, star-forming galaxies) are less likely to be common hosts for FRBs. This is also consistent with an independent study which compared the host galaxy properties of FRBs with those of stellar transients such as Type Ib/Ic supernovae (SN Ibc), Type II supernovae (SN II), Type Ia supernovae in addition to long and short GRBs [167] and work of Wang et al [168] which showed that the compact mergers can account for the observed offset distribution of localised FRBs.…”
Section: Frb Host Galaxy Environmentssupporting
confidence: 91%
“…Bhandari et al [165] and Heintz et al [166] agreed that compact merger events (WD-WD, NS-NS mergers), accretion-induced WD collapse and CCSNe seem to be plausible mechanisms for the FRBs localised by ASKAP and that the galaxies hosting LGRBs (faint, star-forming galaxies) are less likely to be common hosts for FRBs. This is also consistent with an independent study which compared the host galaxy properties of FRBs with those of stellar transients such as Type Ib/Ic supernovae (SN Ibc), Type II supernovae (SN II), Type Ia supernovae in addition to long and short GRBs [167] and work of Wang et al [168] which showed that the compact mergers can account for the observed offset distribution of localised FRBs.…”
Section: Frb Host Galaxy Environmentssupporting
confidence: 91%
“…Metzger, Berger & Margalit 2017), or NS mergers (e.g. Margalit, Berger & Metzger 2019;Wang et al 2020a), so that they have relatively short (e.g. millisecond) periods at births (Usov 1992;Zhang & Mészáros 2001;Metzger et al 2011).…”
Section: Nat U R E O F F R B P Ro G E N I To R Smentioning
confidence: 99%
“…One possible scenario would be to invoke an NS-NS post-merger stable magnetar that can survive the merger (e.g. Zhang & Mészáros 2001;Metzger et al 2008;Bucciantini et al 2012;Rezzolla & Kumar 2015;Margalit et al 2019;Wang et al 2020). However, this requires a stiff NS equation of state and small masses in the NS-NS merger systems.…”
Section: Constraints On the Possible Originsmentioning
confidence: 99%